Driving Farmer-Centered Digital Transformation in African Agriculture - Rupavatharam, Srikanth; Patil, Mukund; Kumar, Shalander; Jat, M.L. (International Crops Research Institute for the Semi-Arid Tropics, 2024)
The event, organized by the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), in collaboration with the Kenya Agricultural and Livestock Research Organization (KALRO) under the aegis of CGIAR initiative on digital innovation, brought together a diverse group—including government representatives, NGOs, private companies, and farmer collectives—to explore how digital agriculture can revolutionize the region's farming practices.